Improved integer programming models for simple assembly line balancing and related problems. (13th September 2015) - Ritt, Marcus; Costa, Alysson M.
Abstract: We propose a stronger formulation of the precedence constraints and the station limits for the simple assembly line balancing problem. The linear relaxation of the improved integer program theoretically dominates all previous formulations using impulse variables, and produces solutions of significantly better quality in practice. The improved formulation can be used to strengthen related problems with similar restrictions. We demonstrate their effectiveness on the U‐shaped assembly line balancing problem and on the bin packing problem with precedence constraints.